2013
DOI: 10.1177/1403494813487449
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported learning difficulties and dietary intake in Norwegian adolescents

Abstract: Having a less-frequent intake of unhealthy foods and not skipping meals are associated with decreased odds of self-reported learning difficulties in Norwegian adolescents in this study. The results of this study support the need for a larger study with a more representative sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 27 publications
1
72
0
2
Order By: Relevance
“…A small number of studies have employed screening questions, asking if the participants believe they have LD (e.g. Patterson, Moniruzzaman, Frankish, & Somers, 2012;Øverby, Lüdemann, & Høigaard, 2013). In the Patterson et al study (2012) two questions predicted several outcomes (e.g., educational attainment, mental and substance abuse problems), thus showing that brief measures may have acceptable validity, but we considered two questions as too narrow in our study.…”
Section: An Important Factor Impeding a Self-autonomous Learning Procmentioning
confidence: 77%
“…A small number of studies have employed screening questions, asking if the participants believe they have LD (e.g. Patterson, Moniruzzaman, Frankish, & Somers, 2012;Øverby, Lüdemann, & Høigaard, 2013). In the Patterson et al study (2012) two questions predicted several outcomes (e.g., educational attainment, mental and substance abuse problems), thus showing that brief measures may have acceptable validity, but we considered two questions as too narrow in our study.…”
Section: An Important Factor Impeding a Self-autonomous Learning Procmentioning
confidence: 77%
“…Whereas most of the previously published studies have focused on the effect of breakfast consumption, Kim and coworkers [9] reported a general association between the consumption of regular meals, including breakfast, lunch and dinner, and academic achievement in Korean children. Furthermore, a less frequent intake of unhealthy foods and not skipping meals was associated with a decreased odds of self-reported learning difficulties in Norwegian adolescents [10], while having a low overall diet quality was associated with a low academic score in Canadian children [11]. …”
Section: Introductionmentioning
confidence: 99%
“…They found that performance in Icelandic, Mathematics and foreign languages was negatively influenced by poor dietary habits, although both studies used self-reported averaged grades to measure academic outcomes. In Norwegian 9th and 10th grade adolescents (n 475), Øverby et al observed that a high intake of foods representing a poor diet was significantly associated with increased odds of mathematical difficulties (23) . In previous research using the same sample, Øverby and Høigaard had found that receiving an optimal diet was linked with decreased odds of behavioural problems at school (24) .…”
Section: Main Conclusionmentioning
confidence: 99%
“…Studies of nutrition and academic performance and/or behaviour have typically focused on the effect of malnutrition and micronutrient deficiency (19,20) . Very few have addressed the effect of overnutrition and they have been mostly carried out in developed countries (21)(22)(23)(24)(25) . Due to the lack of evidence from countries undergoing transitional processes, the aim of the present study was to examine the association between diet as a composite measure and academic outcomes in children from Chile, a middleincome country that underwent a profound shift from under-to overnutrition in less than two decades (26)(27)(28) .…”
mentioning
confidence: 99%